Ein Verbundmodell für Stahlbeton unter Berücksichtigung der Betonschädigung - Auer, Michael (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2015)
The reason for this research are the differences of the bond stress-slip relationships between pullout, push-in and tension tie specimen. A general admitted bond stress-slip law is developed which bases upon analytical consideration. The new developed bond stress-slip law considers the three-dimensional stress state of concrete in front of the rib of the reinforcing bar.